UJI PARAMETER KIMIA BATU GAMPING SEBAGAI BAHAN BAKU SEMEN PADA LOKASI PENAMBANGAN CV THIAK KELURAHAN ARDIPURA KOTA JAYAPURA - Rumabar, Anna Maria; Gaspersz, Rolling Swempry (DINAMIS, 2021)
Limestone mining owned by CV Thiak, which is located in the Ardipura II Jayapura city, has been operating for a long time. However, the utilization of limestone is only used as a mixed material in construction such as offices, schools, brdges and others. One sample of the use og limestone is a raw material for making cement. This study aims to determine the chemical content of limestone belonging to CV Thiak so that it can also be used as a raw material for making cement. The research stage is at the beginning with initial of reaserch location and mapping to determine the coordinates of the sampling location. Samples were taken at two different locations. Next, the stage of taking limestone as a sample for testing. The next stage is the description of the limestone to determine of type of limestone. The stage of sending limestone samples to the Mineral Engineering Laboratory in Bandung city to determine the chemical content contained in the sample. The last stage is the analysis of chemical parameters as data from laboratory test using the X-Ray Fluoresence method. Some of the chemical parameters analyzed were CaCO3, CaO, MgO, Al2O3, Fe2O3 and SiO2. From the results of the analysis, it is known that the two limestone sample belonging to CV Thiak have very high CaCO3 content. The CaCO3 at the first point has a level of 98,78 %. Meanwhile, the sample at the second point has a CaCO3 content of 98,38 %. For levels of CaO, the first point is 55,35 % and the second point is 55,13 %. By looking at the value of the content of CaCO3 and CaO, the quality of CV Thiak’s limestone is very good and meets the standars as cement raw materials, according to Portland cement standards